Facies evaluations and paleoenvironmental reconstruction of the turonian nkalagu formation, south eastern Nigeria (2012)
The Turonian Nkalagu Formation exposed at NIGERCEM (Nigerian Cement Company) within the Lower Benue Trough was studied in this work in order to determine and establish the lithostratigraphic successions and reconstruct the paleoenvironment of the deposition. Two major litho-facies were delineated. The first is matrix-supported bioclastic shell lag wackestone facies which account for about 70% of the carbonates. The second is a massive fossil-poor micritic limestone. However, using the fossil contents, five distinct micro-biofacies were recognized namely: massive lithoclastic floatstone, bioclastic wakestone, siliceous fossil-poor limestone, bioclastic (bivalve debris) wackestone and bioclastic packstone. The litho-clast consists of probably shallow water transported materials while still in various degrees of lithification from shelf into deeper basin. Many of the lithoclasts are sub-angular whereas others have rounded shape. Textural gradient was upward fining and algae were completely absent which is typical of shallow calcareous marine sediments of the photic zone. The trends of the textural characteristics fall in pattern correlatable with the different facies outlined in the study. Thus, the evidence from this study has put Nkalagu Formation as a deposition in shallow marine environment but later displaced into relatively deeper water, probably that of the off-shelf zone, by some sedimentary flow mechanisms.